Synthesis and Bioactivity of Some New 3-Alkyl-2,4-diisopropyl-1,2,4,5-tetrahydro-benzo[e][1,3,2]-diazaphosphepine 3-sulfides/selenides - Ch. Mohan; C. Naga Raju; A. Janardhan Rao (E-Journal of Chemistry)
Preparation of a series of novel seven membered heterocyclic compounds, 3-alkyl-2,4-diisopropyl-1,2,4,5-tetrahydro-benzo[e][1,3,2] diazaphosphepine 3-sulfides / selenides (8a-l) was accomplished in four steps. The synthetic route involves α,α′-dibromo-o-xylene (1) with two moles of isopropylamine (2) in the presence of triethylamine (TEA) in dry tetrahydrofuran (THF) at low temperature to form the compound 3. This on treatment with phosphorus tribromide (4) in the presence of TEA in dry THF to form the corresponding phosphorobromodite (5). This on subsequent reaction with different Grignard reagents (6) in dry THF under N2 atmosphere formed the compounds 7. They are converted to the corresponding sulfides and selenides (8a-l) by reacting them with sulfur and selenium respectively. Their structures were established by elemental analysis, IR, 1H, 13C, 31P NMR and mass spectral data. All the title compounds were screened for their antibacterial activity. Most of the compounds exhibited significant antimicrobial activity.